Study on the Customers’ Attitude Towards the Purchase of Two Wheelers during Pandemic - MUTHUKRISHNAN, R; AMAN, M.S. SHAKEEL; KAVYA, R. P.; DEEPAK, P. (The journal of contemporary issues in business and government, 2021)
Consumer attitude is the feeling of favourableness or unfavourableness that an individual has towards an object. As we, all know that an individual with a positive attitude is more likely to buy a product and this results in the possibility of liking or disliking a product. Consumer attitude basically comprises beliefs, feelings and behavioural intentions towards some objects. This paper highlights the customer’s attitude towards the purchase of two wheelers during covid-19. For this study, the population around Coimbatore region was taken and data was collected using questionnaires from the 151 respondents. Health and safety have become a paramount concern and simultaneously consumer purchasing power has changed in the recent economic conditions. This study focuses on consumer attitudes and preferences while purchasing a vehicle. Vehicle selection is considered to be a multiple criteria decision- making problem. The study is used to determine consumer preferences towards vehicle selection using the following criteria: financial aspects, safety aspects, vehicle features, and services offered.